(untitled) (Revista Logos Ciencia & Tecnología, 2019)
A research relating Consumer Based Brand Equity and students’ permanence intention in the educative institution, was performed. A descriptive correlational study was carried out, using a non-probabilistic sampling with 453 participants in total, which answered a survey that included the variables used by Colombian National Education Ministry (Ministerio de Educación Nacional de Colombia) to measure permanence actions as well as other variables related with the brand equity model, which werespecifically developed for the main purposes of this study. The most important results suggest a positive association between internationalization processes and the permanence intention in the institution; a correlation between perception of the permanence actions and the brand equity in the Superior Education Institution (IES, because of their acronym in Spanish); in the same way, a strong connection between Keller’s Brand resonance model and the Institutional Abandonment of Tinto’s. This evidenced relationship would allow the strengthen of permanence and lowering of student’s abandonment.